2014
DOI: 10.1371/journal.ppat.1003968
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Retroviral Restriction Gene Fv1: Inhibition of Non-MLV Retroviruses

Abstract: Fv1 is the prototypic restriction factor that protects against infection by the murine leukemia virus (MLV). It was first identified in cells that were derived from laboratory mice and was found to be homologous to the gag gene of an endogenous retrovirus (ERV). To understand the evolution of the host restriction gene from its retroviral origins, Fv1s from wild mice were isolated and characterized. Most of these possess intact open reading frames but not all restricted N-, B-, NR-or NB-tropic MLVs, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 66 publications
10
103
3
Order By: Relevance
“…Understanding how these gene transfers influence the immunologic distinction between host "self " and viral "nonself " is of practical importance. Interestingly, several host genes derived from retroviruses limit infection by related viruses (Ikeda and Odaka 1983;Hainaut et al 1990;Mura et al 2004;Aswad and Katzourakis 2012;Fujino et al 2014;Yap et al 2014), demonstrating that lateral gene flow from viruses to their vertebrate hosts can mediate transgenerational immune memory; all known examples are mediated by production of dominant negative proteins. RNA-mediated transgenerational antiviral immunity, while common via the CRISPR/Cas system in prokaryotes (Sorek et al 2008), has thus far been reported in only one metazoan, Caenorhabditis elegans (Rechavi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how these gene transfers influence the immunologic distinction between host "self " and viral "nonself " is of practical importance. Interestingly, several host genes derived from retroviruses limit infection by related viruses (Ikeda and Odaka 1983;Hainaut et al 1990;Mura et al 2004;Aswad and Katzourakis 2012;Fujino et al 2014;Yap et al 2014), demonstrating that lateral gene flow from viruses to their vertebrate hosts can mediate transgenerational immune memory; all known examples are mediated by production of dominant negative proteins. RNA-mediated transgenerational antiviral immunity, while common via the CRISPR/Cas system in prokaryotes (Sorek et al 2008), has thus far been reported in only one metazoan, Caenorhabditis elegans (Rechavi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Also in mice, the capsid-binding restriction factor Fv1 was found to be derived from the gag gene of an ERV (Best et al, 1996). Fv1 protects against infection by a number of exogenous retroviruses by interacting with the capsid and blocking viral DNA entry into the nucleus (Yap et al, 2014). Thus, these restriction factors provide endogenous viral-element-derived immunity by protecting the cell from exogenous retrovirus infection.…”
Section: Expression and Biological Roles Of Hervsmentioning
confidence: 99%
“…Interestingly, the Fv1 alleles isolated from mouse species other than Mus musculus show remarkable diversity in the “target” viruses that they restrict (see below) (Yap et al, 2014)…”
Section: Fv1 Restrictionmentioning
confidence: 99%
“…This presumably reflects ongoing evolutionary battles between viruses and their hosts (Meyerson and Sawyer, 2011); these battles evidently began well before the appearance of contemporary MLVs (Qi et al, 1998; Yan et al, 2009). Indeed, Fv1 loci isolated from different mice can restrict a wide spectrum of retroviruses, including the lentivirus equine infectious anemia virus and the spumaretrovirus feline foamy virus (Yap et al, 2014). It is striking that several of the residues showing evidence of positive selection have previously been identified as critical for restriction of MLVs (Yan et al, 2009).…”
Section: Fv1 Restrictionmentioning
confidence: 99%
See 1 more Smart Citation